A Cognitive Study of Conceptual Metaphor of Hawthorne’s The Scarlet Letter - Esraa Neamah Mohsin; Hussein Musa Kadhim Al- Nasrawi (مجلة الباحث, 2025)
This study explores the use of conceptual metaphors in The Scarlet Letter through Appraisal Theory. While previous studies have examined metaphor and literary analysis, there has been no specific study on the relationship between conceptual metaphors and Appraisal Theory in this work. This study aims to fill that gap by systematically analyzing how metaphorical language influences the novel's themes.